Geochemistry of Bivalve Shells As Indicator of Shore Position of the 2nd Century BC. (24th January 2020) - Mouchi, Vincent; Emmanuel, Laurent; Forest, Vianney; Rivalan, André
In an area named Mermian (municipality of Agde, South of France), a significant amount of fragmented italic amphorae from the 2 nd century BC was discovered, located at a depth of 6 to 8 meters under the bed of the Hérault river. As no ship wreck was found in the vicinity, the reason of the presence of these amphora fragments, whose faces present a large accumulation of oyster shells, is unknown. Reconstructed geomorphological maps of the area present Mermian as a riverine site already at this period, and several hypothetical explanations on the role of these amphorae exist (landfill linked to a neighbouring habitat, bank reinforcement linked to a ford crossing, river landing, etc.). In order to define whether the amphorae were transported to this location and from where, we analysed the stable carbon and oxygen isotopes of the oyster shells. The δ 13 C and δ 18 O indicate that all oysters lived in the same environment, refuting a potential transport during the oyster accumulation. Moreover, the analysis of Mytilaster sp. shells in the sediment around the oyster shells also reported a marine origin, suggesting that these oysters were also buried in a marine deposit. Transport to Mermian from a coastal locality is unlikely but may still have happened, although no trace of human handling were observed on the fragments. Still, the presence of other marine or brackish molluscs in the sediment discards the interpretation of Mermian being a continental locality.